Kontribusi Cendekiawan Muslim dalam Membangun Peradaban Islam - Hamid Fahmy Zarkasyi; Fadhillah Rachmawati (Tasfiyah: Jurnal Pemikiran Islam, 2020)
This articles aims with reference to three major periods of Islamic history, spesifically the period of the caliphate, colonial and independence (post-colonial). The author in this article also proves that the triumph and development of science in Islam cannot be separated from the role and contribution played by Muslim scholars from the process of writing, transitioning science, to transliteration and producing a monumental work that is beneficial to humanity. The process of Islamization of knowledge does not stop from one generation but is passed on to the next generation, starting from the revelations conveyed by the Prophet Muhammad to his companions, tab'īn, tābīut tābi'īn and passed on from one scholars to another. Thus, it can be concluded that since the time of the Prophet Muhammad SAW has introduced key concepts that are in accordance with the Islamic worldview which accumulates in the īman, islām and iḥsān.